The Hideouts of the Vaccination Process - Stefanescu, Alexandru Mihai; Stefanescu, Alexandra Rodica (Journal of Economic Development, Environment and People, 2019)
The purpose of the study is to evaluate the degree of information and the population opinion regarding the vaccination process. The paper aims to evaluate both the reasons of decreasing the vaccination degree and the sources of wrong information on this topic to better identify between mistakes and correct knowledge. Vaccines are biological products prepared following specifical tehcniques to improve the body's immunity against particula, given conditions. The lives of millions of children from 188 countries who received different vaccines (diptero-tetanus-pertussis, measles, polio) were saved in the world along the time (WHO, 2017). In Romania, the antidifteric vaccination introduced in 1960 made disappear the disease in 1990. No case of diphtheria has been confirmed so far. Unfortunately, in 2016, the vaccine coverage has fallen below 90% (CNSCBT, 2017) because of either parents' refusal and the failure in attending a family doctor. Therefore, today, the society is facing a serious situation caused by: a) insufficient and erroneous information of parents expressing their opposition to vaccination and b) manipulation of organizations against vaccination.